Characteristics of barbell trajectory in snatch, fulfilled by elite female weight-lifters - Antoniuk, O. V.; Pavlyuk, O. S.; Chopyk, T. V.; Pavlyuk, E. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2016)
Purpose: to determine trajectories of elite female weight-lifters` movements. Material: 137 elite sportswomen were tested. Analysis of sportswomen`s bio-kinematic actions was fulfilled with the help of Weight lifting analyzer 3.0 apparatus, Germany. Results: we found correlation of barbell snatch trajectory in respect to different weight categories of sportswomen. General characteristics of barbell trajectory are equal both for men and women. We determined indicators of barbell grip deviation from vertical axis. Optimal barbell trajectory depends on relative length values of body segments and other important factors. Conclusions: it was proved that execution of 2nd type trajectory of barbell horizontal movement is the most wide spread and effective. Such type of trajectory is the most often for high sport results off light weight categories (48-58 kg).